Incidence and type of peripheral intravenous catheter complications documented in hospitalised dogs. (28th November 2022) - Simpson, S. E.; Zersen, K. M.
Abstract : Objective: To report the incidence and type of peripheral intravenous catheter complications in hospitalised dogs. Methods: A prospective, observational trial was performed. Peripheral intravenous catheters were monitored for complications. Complications were documented and classified as extravasation, phlebitis, dislodgement, occlusion and line breakage. If phlebitis was present, the Visual Infusion Phlebitis Scale was used to assign a grade (0 to 5). Fisher's exact test was used to compare the type of complications between the critical care unit and the intermediate care unit. A univariate logistic model was used to compare the incidence of complications between the critical care unit and the intermediate care unit and adjusted odds ratios were used to compare the groups. Results: The incidence of peripheral intravenous catheter complications was 24.2% in the Critical Care Unit and 13.1% in the Intermediate Care Unit, with an overall incidence of 19.9%. Phlebitis was the most common peripheral intravenous catheter complication in the Critical Care Unit, and line breakage was the most common complication in the Intermediate Care Unit. Length of hospitalisation and weight had a significant effect on the likelihood of complication. In a multivariable logistic regression model, the odds of a peripheral intravenous catheter complication was not significantly higher in CCU than IMCU, accounting for length of hospitalisation and weight (adjusted odds ratio, 1.84; 95% confidence interval, 0.98 to 3.48). Clinical Significance: Peripheral intravenous catheter complications are common in hospitalised dogs and may result in an increased expense for owners, failure to deliver prescribed treatments, venous depletion (lack of peripheral vessels for intravenous catheter placement) and pain experienced by the patient. Techniques to reduce peripheral intravenous catheter complications should be further evaluated and may include the use of peripheral intravenous catheter placement and maintenance checklists, use of force‐activated separation devices, or patient sedation.